Heat transfer enhancement of turbulent flow in a channel with diamond shaped baffles - Saim, Rachid; Benzenine, Hamidou; Öztop, Hakan Fehmi; Al-Salem, Khaled (Inderscience Enterprises Ltd, 2013)
A numerical study was conducted on turbulent flow in a rectangular duct with diamond shaped baffles placed on the top and bottom walls. The governing equations, based on the low Reynolds number k-epsilon model, are solved to describe the thermohydraulic behaviour of the fluid using the finite volume method. Velocity profiles and drag coefficient were obtained and presented for selected locations along the duct, namely, upstream, downstream and between the two diamond shaped baffles. The results were compared with available experimental and numerical data from literature. The highest value of the normalised Nusselt number was attained when the baffles were tilted five degrees from the vertical.
Keywords: computational fluid dynamics; CFD; shaped baffles; channel; turbulent flow; numerical solution